SCIENTIFIC EXPEDITIONS OF THE RUSSIAN EMPIRE IN KAZAKHSTAN AS A MECHANISM FOR THE FORMATION OF COLONIAL KNOWLEDGE (LATE 19TH – EARLY 20TH CENTURIES) (Journal of history-rus, 2026)
The purpose of this study is to examine scientific expeditions of the Russian Empire conducted in the territory of Kazakhstan in the late nineteenth and early twentieth centuries as a mechanism for the formation of colonial knowledge. The research aims to identify the role of expeditionary materials in the accumulation, systematization, and interpretation of data on the socio-economic, demographic, and economic characteristics of the region within the framework of imperial scientific and administrative practices. In this context, the study provides a historiographical and source-critical analysis of scientific and statistical expedition materials.Methods: The research is based on a combination of historical analysis and source criticism. Comparative-historical methods, as well as methods of analysis and synthesis, are used to examine expeditionary data and to determine their relevance to the studied period. In addition, retrospective, structural-analytical, and comparative approaches are applied, allowing scientific expeditions to be considered as an institutional mechanism for the production and legitimization of colonial knowledge. Particular attention is paid to the principles of data collection, classification, and use within imperial scientific discourse.Results: The study demonstrates that the materials of scientific expeditions of the Russian Empire played a key role in shaping systematic knowledge about Kazakhstan. It is established that a significant portion of expeditionary sources belongs to descriptive and analytical documents reflecting the socio-economic and economic characteristics of the region. The analysis shows that the collected data were used not only for scholarly purposes but also in imperial administrative practice, which influenced the methods of interpretation and structuring of knowledge.Conclusions: The study concludes that scientific expeditions of the Russian Empire constituted an important mechanism for the formation of colonial knowledge about Kazakhstan in the late nineteenth and early twentieth centuries. On the one hand, expeditionary materials represent the results of scientific research; on the other hand, they reflect the objectives and interests of imperial governance. The author argues that the analyzed sources can be classified into socio-economic and administrative-statistical materials based on their content.